Answer:
(-4,-2) and (-2, -2)
Explanation:
Eliminate y by equating the two given equations:
y=-x^2-6x-10
y = 3x^2 + 18x + 22 = -x^2 - 6x - 10.
Next, combine like terms, obtaining: 4x^2 + 24x + 32 = 0
Simplify by dividing all terms by 4: x^2 + 6x + 8 = 0.
Factor: x^2 + 6x + 8 = 0 => (x + 4)(x + 2) = 0.
Solve for x: x = -4 and x = -2.
Find the y-values associated with these x-values:
y = -(-4)^2 - 6(-4) - 10 = -16 + 24 - 10 = -2, so that one solution is (-4,-2)
y = -(-2)^2 - 6(-2) - 10 = -4 + 12 - 10 = -2, so that the other sol'n is (-2, -2).